Beyond intervalley transfer: damped Bloch oscillation and negative differential drift velocity at very high fields in wide bandgap III‐nitride materials. Issue 3 (19th March 2014) - Yoder, P. Douglas; Sridharan, Sriraaman
Abstract: We present evidence for a new mode of charge transport at very high fields in gallium nitride (GaN) and related wide bandgap materials, based on the phenomenon of damped Bloch oscillation. Entirely new solutions of the Boltzmann transport equation (BTE) are developed to describe the microscopic physics of damped Bloch oscillation, which is shown to lead to negative differential drift velocity in bulk material. Bloch transport in bulk GaN is confirmed by full band Monte Carlo simulation. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)